Pendampingan Mahasiswa MBKM KKNT dalam Perencanaan Daerah Wisata Kuta Rayat, Kecamatan Naman Teran, Kabupaten Karo - Rahmadhani Fitri; Septian Tri Bagaskoro; Putra Peliks Arianto Purba (Fakultas Teknik Universitas Cenderawasih, 2024)
The village tourism program continues to grow as alternative tourism is expected to make a positive contribution to community development. Efforts to develop and manage resources must be directed so that they can fulfill economic, social, and aesthetic aspects while maintaining the integrity and or preservation of ecology, biodiversity, culture, and living systems. Kuta Rayat is one of the villages in the Naman Teran sub-district, Karo Regency, North Sumatra Province, Indonesia. Kuta Rayat Village is one of the villages planned to become a tourist village. The mentoring activities were carried out in 2023 and involved academics and students of the Architectural Engineering Study Programme of Universitas Panca Budi Medan. The mentoring method was carried out through Focus Group Discussion (FGD). The results of the assistance explained that tourism villages have an important role for many aspects, one of which is spurring the potential for the growth of the creative economy in the local environment, as well as opening up employment opportunities for residents who are close to tourist sites. Kuta Rayat Village has a lot of potential to be developed into a tourist area. Through the development of the potential of existing resources, villages in Indonesia, especially the Karo Regency area, are expected to become attractive and sustainable tourist destinations and the main target of tourism village development is to improve the welfare of the surrounding community.